卷积交换律

卷积交换律

证明:
( f ∗ h ) [ m , n ] = ∑ i = − ∞ ∞ ∑ j = − ∞ ∞ f [ i , j ] ⋅ h [ m − i , n − j ] = − ∑ p = ∞ − ∞ ∑ q = ∞ − ∞ h [ p , q ] ⋅ f [ m − p , n − q ] = ∑ p = − ∞ ∞ ∑ q = − ∞ ∞ h [ p , q ] ⋅ f [ m − p , n − q ] = ( h ∗ f ) [ m , n ] (f*h)[m, n] = \sum_{i=-\infty}^\infty\sum_{j = -\infty}^\infty f[i, j]\cdot h[m-i, n-j]\\ = -\sum_{p=\infty}^{-\infty}\sum_{q=\infty}^{-\infty}h[p, q]\cdot f[m-p, n-q]\\ =\sum_{p=-\infty}^{\infty}\sum_{q=-\infty}^{\infty}h[p, q]\cdot f[m-p, n-q]\\ = (h*f)[m, n] (fh)[m,n]=i=j=f[i,j]h[mi,nj]=p=q=h[p,q]f[mp,nq]=p=q=h[p,q]f[mp,nq]=(hf)[m,n]

Q . E . D Q.E.D Q.E.D

©️2020 CSDN 皮肤主题: 鲸 设计师:meimeiellie 返回首页